PROYEKSI PRODUKSI IKAN HASIL TANGKAPAN DI PELABUHAN PERIKANAN SAMUDERA KUTARAJA PROVINSI ACEH - Kurnia Kurnia; Mustaruddin Mustaruddin; Ernani Lubis (Jurnal Teknologi Perikanan dan Kelautan, 2019)
PPS Kutaraja is a very strategic port and is being developed by the Government of Aceh to become the economic center of fisheries. This study aims to analyze the production of captured in PPS Kutaraja and project the production of captured fish for the year (2020-2024). The research was conducted in June-July 2019. The method used was a case study with forecast analysis using a simple linear ranking model and calculating the value of determination and SEE. Based on the analysis, it is known that the development of IHT production in 2012-2018 has increased every year with an average of 17%. Forecasting results for 2020 reached 92.637,85 ton, in 2021 reached 159.162,54 ton, in 2022 it reached 260.598,23, in 2023 it reached 268.820,21 ton, and in 2024 reached 272.978,67 ton. The conclusion is the forecasting of production results has increased very dramatically in the next 5 years.